Alfresco CMIS. - Bergljung, Martin (Community experience distilled., 2014)
The book will show readers how to use Alfresco's implementation of CMIS through a tutorial-based approach. Alfresco CMIS is for developers, integrators, and IT consultants, who plan to integrate CMIS repositories with other systems or to build applications that interact with a CMIS repository. The book assumes some familiarity with core concepts of the Alfresco architecture and with the principles of content management, but there are no extensive developer prerequisites.